PERANCANGAN DAN PEMBUATAN REKAM MEDIS ELEKTRONIK BERBASIS WEB DENGAN MEMANFAATKAN QR CODE DI PUSKESMAS KARYA MAJU KABUPATEN MUSI BANYUASIN - Detty Artin Meirina; Sustin Farlinda; Feby Erawantini; Muhammad Yunus (Politeknik Negeri Jember, 2022)
Information technology provides many conveniences in the management and can process data and information, then distribute it more efficiently, flexibly, and accurately. Information technology is also adopted in the health sector to produce information in making a decision relating to the management of health services and to support the implementation of health development managed by health information systems. Data and information on health information systems are obtained from medical records documents, so medical record documents must have good quality information. The problems found at Puskesmas Karya Maju are a manual recording of medical record documents. Sometimes, officers have difficulty finding medical records documents because the officer mistakenly put the medical record documents into their places, leading to a lack of quality of the resulting data information. This research aims to design and create web-based electronic medical records with the QR Code, which are expected to overcome the problems arising from the manual recording and processing of medical records. The type of research used is qualitative research with the Waterfall system method consisting of analysis, design, coding, and testing. Data collection techniques using interviews, documentation, and observations. The result of web-based electronic medical records equipped with QR Code is when the patient comes back for treatment, and the patient does not need to bring KIB. The patient needs to bring a smartphone that has been logged in with the patient’s account, and the officer will scan the QR Code to find the patient’s identity and medical records.